Calcimicrobial-archaeocyath-bearing clasts from marine slope deposits of the Cambrian Mount Wegener Formation, Coats Land, Shackleton Range, Antarctica - Rodriguez-Martinez, M.; Perejon, A.; Moreno-Eiris, E.; Menendez, S.; Buggisch, Werner (Estudios Geológicos, 2019)
The carbonate clasts from the Mount Wegener Formation provide sedimentological, diagenetic and palaeontological evidences of the destruction and resedimentation of a hidden/unknown Cambrian carbonate shallow-water record at the Coats Land region of Antarctica. This incomplete mosaic could play a key role in comparisons and biostratigraphic correlations between the Cambrian record of the Transantarctic Mountains, Ellsworth-Whitmore block and Antarctic Peninsula at the Antarctica continent. Moreover, it represents a key record in future palaeobiogeographic reconstructions of South Gondwana based on archaeocyathan assemblages.
CRIS-Team WoS Importer:2020-01-14